(untitled) (Tanzania Medical Journal, 2021)
Background At a time when efforts to reduce maternal mortality have been stepped up, it is important to look at mothers’ satisfaction with institutional delivery and factors associated with it. According to WHO the main goal of health care is to deliver equitable, effective, and accessible health care, which will provide client satisfaction. Thus, this study aimed at assessing the mothers’ level of satisfaction with institutional delivery services and factors associated with it. Method It was a hospital-based analytical cross-sectional study. A multistage sampling technique was used to obtain a sample size of 329 respondents. An interviewer-administered structured questionnaire was the main method used for data collection. Data were analyzed by statistical package for social science (SPSS) version 20. Multivariate and binary logistic regression was applied to identify factors associated with satisfaction with delivery services. Result Mother's satisfaction with institutional delivery was 188/329 (57.1%). Half of the respondents 168/329 (51.1%), 166/329 (50.5%) and 173/329 (52.6%) were satisfied with privacy, waiting time and health workers’ communication, respectively. The majority 208/329 (63.2%) were dissatisfied with perceived attendants’ competencies. Predictors of satisfaction were age group >20years (AOR=3.149, 95% CI 1.169-8.481 p=0.023) and 30 years and above (AOR=4.421, 95% CI 1.451-13.474 p=0.006) and employment (AOR=1.936, 95%Cl 1.190-3.150, p=0.008). Conclusion Substantial numbers of post-delivery mothers were not satisfied with institutional health delivery services. Young women and unemployed were less likely to be satisfied with institutional health deliveries. The study recommends an interventional study, which will determine cost-effective strategies to improve satisfaction with health facility delivery.